2017
DOI: 10.1097/mpa.0000000000000917
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Treatments on Diabetic Control and Gastrointestinal Symptoms After Total Pancreatectomy

Abstract: After TP, CSII therapy is safe compared with MDIs in T3cDM and not associated with an increase in severe hypoglycemic events. Pancreatic enzyme replacement therapy is highly variable with low doses associated with unintentional weight loss and gastrointestinal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Moreover, recent studies have reported improved perioperative outcomes and postoperative QoL after TP, presumably due to centralization at high-volume centers and development of long-acting insulin and modern pancreatic enzyme preparations. 1014…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent studies have reported improved perioperative outcomes and postoperative QoL after TP, presumably due to centralization at high-volume centers and development of long-acting insulin and modern pancreatic enzyme preparations. 1014…”
mentioning
confidence: 99%
“…Moreover, recent studies have reported improved perioperative outcomes and postoperative QoL after TP, presumably due to centralization at high-volume centers and development of long-acting insulin and modern pancreatic enzyme preparations. [10][11][12][13][14] Postoperative pancreatic fistula (POPF) is the main cause of surgical morbidity after pancreatoduodenectomy (PD). Several risk score systems based on pre-and intraoperative parameters, such as the fistula risk score (FRS) or the alternative fistula risk score (a-FRS), have been proposed to predict the occurrence of POPF and stratify patients based on this risk.…”
mentioning
confidence: 99%
“…We identified no difference in glycemic control or insulin dose between the CSII group and the MDI group, but Struyvenberg et al. ( 26 ) demonstrated a significant reduction in severe hypoglycemic events in the CSII group than in the MDI group. Additionally, it was reported that artificial pancreas, sensor-augmented predictive low-glucose suspend pump and advanced hybrid closed−loop systems were efficacious and safe for perioperative and long-term glycemic control after TP ( 39 41 ).…”
Section: Discussionmentioning
confidence: 52%
“…Recently, the focus on hyperglycemia control in perioperative patients with diabetes has increased, and experience is gradually being accumulated in this regard 8 9 10 11 12 13 . An increasing number of evidences suggest the superiority of CSII over MDII during the perioperative period in patients with diabetes 14 15 . A study 16 found that compared with MDII, even short-term implementation of CSII could improve the postoperative control of glucose and reduce the incidence of postoperative fever in surgical patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%